ASSOCIATION BETWEEN HELMINTH INFECTIONS AND EOSINOPHIL AND TOTAL IMMUNOGLOBULIN E IN SEROPOSITIVE PATIENTS (Vietnam Journal of Community Medicine, 2026)
Background: Helminth infections are common parasitic diseases in humans, particularly zoonotic helminths that directly affect human health. Following parasitic invasion, the human body exhibits multiple responses that represent both consequences of parasitism and protective immune mechanisms. These responses can be detected through cellular, tissue, and serological changes, including leukocytosis, eosinophilia, and increased total immunoglobulin E (IgE).Objective: To determine the prevalence of eosinophilia and total IgE antibodies among individuals seropositive for helminth infections and to evaluate the association between helminth infection, eosinophil counts, and total IgE levels.Methods: A cross-sectional descriptive study was conducted from January 2023 to November 2023 on 503 patients with positive serological tests for helminths at the outpatient clinic of the Institute of Malariology, Parasitology and Entomology Quy Nhon.Results: All seropositive helminth groups showed high total IgE positivity rates (>80%), with the highest in Toxocara canis (86.8%) and the lowest in Echinococcus sp. (75.8%). Patients aged >60 years had the highest IgE positivity rate (91.7%), whereas the highest mean total IgE concentration was observed in the 6–15 age group (912.8 IU/mL). Eosinophilia rates were relatively low (20%. The T. canis-positive group had the highest percentage of elevated total IgE at 86.8%, but the highest average total IgE concentration was observed in C. cellulosae: an average of 1017.08 IU/ml. The S. stercoralis-positive group had the lowest average total IgE concentration among the parasites, with an average of 636.49 IU/ml. The associations between eosinophilia and total IgE in patients seropositive for S. stercoralis, G. spinigerum and Fasciola spp. were statistically significant. The Toxocara canis positive group has a higher total IgE than eosinophils, while Cysticercus cellulosae has a higher total IgE eosinophils than total IgE.Conclusions: The greater the number of helminth species infecting an individual, the higher the rate and concentration of total IgE. Among helminth-infected patients, those with eosinophilia exhibited higher concentration of total IgE positivity than those with normal eosinophil counts.
Keywords: Total IgE, eosinophilia, helminth infection